Metacognition of junior high school students in mathematics problem solving based on cognitive style / Sutama ... [et al.] - Adam, Sutama; Anif, Sofyan; Prayitno, Harun Joko; Narimo, Sabar; Fuadi, Djalal; Sari, Diana Purwita; Adnan, Mazlini (Universiti Teknologi MARA, 2021)
The aim of this study was to explain junior high school students' metacognition with Field Independent (FI) and Field Dependent (FD) cognitive styles in mathematics problem solving. The statistical population of this study was all junior high school students in the Sragen regency in the 2018/2019 academic year. Purposive sampling was used to pick the subjects. Different instruments such as the cognitive style tests, the problem-solving exercises, and the interview guidelines were used to reach the research purpose. Moreover, time triangulation was used to ensure data validity. The data has been processed through four stages of data collection, data reduction, data presentation, and conclusion. The results indicated that the students who have field-independent cognitive styles indicated high self-confidence and the ability to solve the problem correctly. They were also able to do planning steps, make important decisions for themselves, and solve the problem properly. However, students with FD cognitive style are completely confident that their answer is correct, but they have not yet clarified the steps they need to solve their problems. They also have not yet focused on their shortcomings in mathematics problem-solving. Hence, their task results in mathematics problem-solving have incorrect answers.